Analisis Rem Cakram Depan Motor Yamaha Jupiter MX 135 CC - Hildane Ramadhan Alfarizy; Aa Santosa; Farradina Choiria Suci (Peneliti.net, 2022)
Braking is a system mechanism designed to reduce the speed of a vehicle, this system is very important in vehicles as a means of safety and ensures that the driver is safe. The work of the brakes is affected by the type of brake used and the load of the vehicle. In the disc braking system, brake pads are one of the components that function to inhibit or reduce the speed of the vehicle. To get maximum braking, brake pads with good braking ability are needed, the quality of the brake pads is determined by the hardness and material of the brake linings. Where the goal is to be able to find out about the front brakes on the Jupiter MX 135 CC motorcycle. and also be able to analyze the disc brakes, and be able to find out the condition, function and working principle of all components on the disc brakes on the front wheels of the Jupiter MX 135 CC motorcycle in this study using quantitative methods, namely by direct measurements of the Jupiter mx 135 CC motorcycle.